EDUKASI PEMANFAATAN LIMBAH ORGANIK SEBAGAI ECO-ENZYME UNTUK PRODUK KESEHATAN BAGI MASYARAKAT RAWA KOPI-DEPOK - Rahmi, Eldiza Puji; Revina, Rika; Farkhani, Aulia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
Waste from the production process in the community around Rawa Kopi, Depok, is one of the problems in their environment that requires further processing. Eco-enzyme is a potential organic waste processing technology and can be an effort to achieve the 12th SDGs goal regarding sustainable production and consumption patterns. This technology involves a fermentation process of organic waste combined with brown sugar/molasses and air in a certain ratio. The eco-enzyme liquid produced is an active ingredient that can be used for various purposes. This community service activity aims to provide outreach and education in utilizing waste, especially organic waste, which can be processed into eco-enzymes for the community around Rawa Kopi, Depok. The activity began with giving a pretest, then socialization about eco-enzymes through lectures and interactive discussions. Evaluation is carried out on the process, including attendance, enthusiasm/enthusiasm, participants' responses to training activities, and post-test material education. The results of the activity will provide knowledge to utilize organic waste around us into eco enzymes, which can then be further utilized into materials such as fertilizer, disinfectant, hand sanitizer and others. Community knowledge and understanding in utilizing organic waste around us into eco enzymes can increase after the activity. The results of the activity were able to provide knowledge about degenerative diseases and the use of Indonesian medicinal plants for degenerative diseases. Community knowledge and understanding of degenerative diseases and recognizing and utilizing plant medicines can increase significantly (p<0.001) after the activity up to 77.57%. ABSTRAK; ABSTRAK Limbah dari proses produksi pada UMKM masyarakat sekitar Rawa Kopi, Depok, menjadi salah satu permasalahandi lingkungan mereka yang memerlukan pengolahan lebih lanjut. Eco-enzyme adalah salah satu teknologipengolahan sampah organik yang potensial dan dapat menjadi salah satu upaya mencapai tujuan SDGs ke-12terkait pola produksi dan konsumsi yang berkelanjutan. Teknologi ini melibatkan proses fermentasi sampah organikyang dikombinasikan dengan gula merah/molase dan air dengan perbandingan tertentu. Cairan eco-enzim yangdihasilkan merupakan bahan aktif yang dapat digunakan untuk berbagai kepentingan. Kegiatan pengabdian kepadamasyarakat ini bertujuan untuk memberikan sosialisasi dan edukasi dalam memanfaatkan limbah terutama limbahorganik yang dapat diolah menjadi eco-enzyme bagi masyarakat sekitar Rawa Kopi, Depok. Kegiatan dimulaidengan pemberian pretest, selanjutnya sosialisasi mengenai eco-enzyme melalui ceramah dan diskusi interaktif.Evaluasi dilakukan terhadap proses yang meliputi kehadiran, semangat/antusiasme, dan respon/tanggapan pesertaterhadap kegiatan pelatihan, serta posttest materi edukasi. Hasil kegiatan diharapkan mampu memberikanpengetahuan untuk memanfaatkan sampah organik di sekitar kita menjadi eco enzyme yang selanjutnya dapatdimanfaatkan lebih jauh menjadi bahan-bahan seperti pupuk, desinfektan, hand sanitizer dan lain-lain.Pengetahuan dan pemahaman masyarakat dalam memanfaatkan sampah organik di sekitar kita menjadi eco enzymebisa meningkat setelah kegiatan. Hasil kegiatan mampu memberikan pengetahuan tentang pemanfaatan limbahorganik sebagai eco-enzyme untuk produk kesehatan. Pengetahuan dan pemahaman masyarakat meningkat secarasignifikan (p<0,001) setelah kegiatan hingga 77,57%.